Effect of RF plasma on Moringa seeds germination and growth - Nagia Dawood (Journal of Taibah University for Science, 2020)
The paper presents the effect of cold plasma (RF-Ar low-pressure plasma) on Moringa oleifera seeds. Five groups of seeds characterized by the different exposure times (1, 5, 10 and 15 mints) as well as untreated seeds. The highest germination parameters were obtained for seeds treated for the exposure times of 1 min. Analysis of the data showed a statistically significant impact of RF plasma on the seeds germination parameters. The surface properties of the plasma-treated samples are examined using scanning electron microscopy (SEM). Improvements appeared in the germination percentage and germination potential of the treated seeds and increase in the length of the plant for seeds exposed to the RF plasma at treatment time 1 and 5 min. from 4,32% to 26.40% for roots and from 15.91 % to 18.62 % for shoots, respectively. Also, it is observed that the weight of seeds increased for the samples treated at 1 and 5 min from 4.89% to 6.22%, and the weight of the shoots is increased from 6.19% to 6.93%.